Haplotype-resolved telomere-to-telomere genome assembly of the dikaryotic fungus pathogen Rhizoctonia cerealis - Jiang-Na Han; Yu Li; Wei Li; Hao-Hao Yan; Fengping Yuan; Huai-Gu Chen; De-Jun Han; Zhen-Sheng Kang; Qing-Dong Zeng (Scientific Data)
Abstract Rhizoctonia cerealis, the causal agent of sharp eyespot, is a highly destructive pathogen of wheat. Despite its global importance, the genetic and molecular mechanisms underlying virulence of R. cerealis remain poorly understood. R. cerealis is a dikaryotic organism and the haplotype phase has been isolated. Based on the PacBio HiFi, Oxford Nanopore, and Hi-C platforms, we assembled the first high quality telomere-to-telomere (T2T) haplotype-resolved genome of R. cerealis, with sizes of 41.50 and 41.05 Mb, and N50 sizes of 2.67 and 2.42 Mb, respectively. High consensus quality values of 57.75 and 57.09 for the two haplotypes validated the accuracy of the assembly. The assembly achieved R-AQI and S-AQI scores of 92.5 and 100, respectively, both indicating reference-level quality. A total 25,353 protein coding genes were predicted for the two haplotypes with a BUSCO score of 96.7%. The genome assembly will serve as the foundation for further research on allele-specific expression, genetic variation and evolution of R. cerealis.